Book Review: "Hara, A.E., Indriastuti, S., & Trihartono, A. (2023). Keamanan Insani (Human Security): Eksplorasi berbagai Perspektif di Dunia. Pandiva. 238 pp." - Rizkyta, Annisa; Al Jannah, Nur Zahrun (Journal of Urban Sociology, 2024)
The book reviewed in this paper examines the concept of human security, which is an expanded perspective of state security. This book by Hara, Suyani and Trihartono offers a comprehensive exploration of the global perspective of human security. While detailing the human security perspectives of the UNDP, Japan, Canada and the European Union, the book also highlights Indonesia's unique position. The book emphasizes the role of Religious Non-State Actors (RNSAs) in addressing human security issues. Using primary data in its final chapter, the book advocates for a reinterpretation of human security in Indonesia that is adapted to diverse social and historical contexts. In addition, this review finds that the in-depth interpretations in this book provide opportunities for further exploration or study for future researchers.Keywords: human security; religious non-state actors; Indonesia